A ATUALIDADE DO PENSAMENTO DE GUERREIRO RAMOS: branquidade e nação - Feres Júnior, João (Caderno CRH, 2015)
<p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">O presente ensaio tem como objetivo mostrar que a reflexão sobre relações raciais no Brasil do sociólogo baiano Guerreiro Ramos, da década de 1950, continha elementos do que mais tarde iria se consolidar como Teoria da Branquidade, cujo ponto fulcral é examinar a constituição do branco em um sistema de relações raciais, e não o “problema do negro”. Em seguida, demonstro como a questão da branquidade, em Guerreiro, está intimamente ligada à sua concepção normativa de nação, para, em seguida, examinar pontos de tensão entre sua concepção e as teorias da negritude, as quais ele bebeu e lhe serviram de inspiração, tanto quanto teorias mais recentes, como as do Atlântico Negro e da Diáspora Africana. Concluo defendendo que as questões apontadas por Guerreiro, como a crítica da branquidade ligada a um projeto emancipador de nação, continuam atuais no mundo de hoje, tanto para o Brasil quanto para o mundo no qual ele se insere. <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Palavras-chave : Guerreiro Ramos; Branquidade; Relações Raciais; Negro; Nação. <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;"><span style="color: #000000; font-family: verdana,arial; font-size: 13.192px; font-style: normal; font-variant: normal; font-weight: bold; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; display: inline ! important; float: none; background-color: #ffffff;">The freshness of Guerreiro Ramos’s thinking: whiteness and nation. João Feres Júnior <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">The goal of this essay is to show that the reflection on race relations in Brazil by sociologist Guerreiro Ramos, in the 1950s, contained elements of what would later consolidate itself as a Theory of Whiteness whose central point is to examine the constitution of whiteness in a system of race relations instead of the “black people issue”. Subsequently, I demonstrate how the issue of whiteness, for Guerreiro, is intimately connected to his normative conception of nation, and then examine tension points between his conception and blackness theories, which he used as source and inspiration, as well as more recent theories, such as Black Atlantic and African Diaspora. I finish the article by arguing that the issues pointed out by Guerreiro, such as the criticism towards the connection of whiteness with an emancipatory nation project, remain fresh in today’s world, as much for Brazil as it is for the rest of the world. <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Palavras-chave : Guerreiro Ramos; Whiteness; Race Relations; Black People; Nation. <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;"><span style="color: #000000; font-family: verdana,arial; font-size: 13.192px; font-style: normal; font-variant: normal; font-weight: bold; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; display: inline ! important; float: none; background-color: #ffffff;">L’actualité de la pensée de Guerreiro Ramos: blancheur et nation. João Feres Júnior <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">L’objectif de l’analyse que nous présentons ici est de montrer que la réflexion faite sur les relations sociales au Brésil par le sociologue bahianais Guerreiro Ramos, dans les années 1950, était dotée d’éléments qui plus tard allaient être consolidés comme Théorie de la Blancheur dont le point crucial est d’examiner la constitution du Blanc dans un système de relations raciales et non pas le « problème du Noir ». Puis, nous démontrons combien la question de la blancheur chez Guerreiro Ramos est intimement liée à sa conception normative de nation pour ensuite vérifier les éléments de tension entre sa conception et les théories de la négritude qu’il a absorbées et qui lui ont servi d’inspiration. Il s’agit autant des théories plus récentes que de celles de l’Atlantique Noir et de la Diaspora Africaine. Pour conclure, nous soutenons que les questions soulevées par Guerreiro, telle la critique de la blancheur liée à un projet émancipateur de nation, sont toujours actuelles dans notre monde d’aujourd’hui autant pour le Brésil que pour le monde dans lequel il s’insère. <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Mots-clés: Guerreiro Ramos. Blancheur. Relations raciales. Noir. Nation. <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;"><small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Publicação Online do Caderno CRH no Scielo: http://www.scielo.br/ccrh<span style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; float: none; display: inline ! important; background-color: #ffffff;"> <br style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;" /> <br style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;" /> <small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br<span style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; display: inline ! important; float: none; background-color: #ffffff;">